2013
DOI: 10.1159/000350878
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up: The Evidence

Abstract: There is currently no consensus on the best strategy for the follow-up of patients who have undergone surgical treatment with curative intent for gastric cancer. The wide variation in recommendations for surveillance among international experts and hospital schedules clearly reflects a lack of an established body of evidence on this subject. Consequently, most of the international guidelines aimed at early detection of disease recurrence gloss over details concerning the mode, duration, and intensity of survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
1
24
0
2
Order By: Relevance
“…However, the role of CT after endoscopic resection is not clear. After surgical resection of gastric cancer, use of abdominal CT has not been shown to improve long-term survival [30,31,34]. In colorectal cancer, several randomized clinical trials and meta-analyses have reported that intensive follow-ups that included CT after curative resection increased the rate of curative surgery for recurrence compared with minimal follow-ups [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of CT after endoscopic resection is not clear. After surgical resection of gastric cancer, use of abdominal CT has not been shown to improve long-term survival [30,31,34]. In colorectal cancer, several randomized clinical trials and meta-analyses have reported that intensive follow-ups that included CT after curative resection increased the rate of curative surgery for recurrence compared with minimal follow-ups [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…A regular follow-up may allow investigation and treatment of symptoms, psychological support and early detection of recurrence, though there is no evidence that it improves survival outcomes [III, B] [98,99]. New strategies for patient follow-up are currently undergoing evaluation, including patient-led self-referral and services led by clinical nurse specialists [103].…”
Section: Follow-up Long-term Implications and Survivorshipmentioning
confidence: 99%
“…Very few trials report anything other than the detection of recurrence or death as their primary endpoints, and the prognostic effect of early detection seems doubtful, given the poor survival of patients with recurrent gc 11 . The limited studies available to date have not shown a survival benefit for the detection of asymptomatic recurrence compared with patient-reported symptomatic recurrence 12,13 . Furthermore, qol constitutes an important omission in the current literature.…”
Section: Summary Of Evidencementioning
confidence: 98%
“…Patient education and self-referral for abnormal symptoms are important. Periodic assessments are useful to address treatment-related complications, nutrition deficiencies (including vitamin B 12 and iron), and psychosocial issues. In patients with a subtotal gastrectomy, eradication of Helicobacter pylori is recommended.…”
Section: Questionmentioning
confidence: 99%